Pendampingan Pelatihan Muhadoroh dalam Meningkatkan Kepercayaan Diri Peserta Didik TPQ Al-Musyahadah - Nury Sri Dimjati (Jurnal Pengabdian Kepada Masyarakat, 2026)
Self-confidence is a fundamental component in the development of students’ character, particularly in supporting Islamic preaching and communication skills. However, empirical conditions indicate that some students in Qur’anic Education Centers (TPQ) still experience challenges such as lack of confidence, anxiety in public performance, and limited public speaking ability. This community service program aims to enhance students’ self-confidence through mentoring-based muhadaroh training. The study employed a descriptive qualitative approach involving stages of observation, material delivery, communication exercises, muhadaroh practice, and evaluation. The program involved 25 students of TPQ Al-Musyahadah. The results demonstrate a significant improvement in students’ confidence, communication skills, and courage in delivering Islamic messages orally. Therefore, muhadaroh training proves to be an effective strategy for character development and strengthening students’ communication competencies.